2003
DOI: 10.1177/002215540305101004
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Serine Protease HtrA1 in Normal Human Tissues

Abstract: The human HtrA family of proteases consists of three members: HtrA1, HtrA2, and HtrA3. In bacteria, the chief role of HtrA is recognition and degradation of misfolded proteins in the periplasm, combining a dual activity of chaperone and protease. In humans, the three HtrA homologues appear to be involved in diverse functions such as cell growth, apoptosis, allergic reactions, fertilization, control of blood pressure, and blood clotting. Previous studies using RNA blot hybridization have shown that the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 20 publications
3
94
0
Order By: Relevance
“…HtrA1 was strongly expressed in astrocytes and cortical neurons (Fig. 4 D-F), whereas expression in neuroglial components and neurons of normal adult brains is always very low (33). In particular, the percentage of neurons overexpressing HtrA1 ranged from 1-2% of cerebellum and occipital cortex to 2-4% of frontal, parietal, and temporal cortex and 8-10% of hippocampus.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…HtrA1 was strongly expressed in astrocytes and cortical neurons (Fig. 4 D-F), whereas expression in neuroglial components and neurons of normal adult brains is always very low (33). In particular, the percentage of neurons overexpressing HtrA1 ranged from 1-2% of cerebellum and occipital cortex to 2-4% of frontal, parietal, and temporal cortex and 8-10% of hippocampus.…”
Section: Discussionmentioning
confidence: 93%
“…4 D-F). In contrast, HtrA1 expression in neuroglial components and neurons of normal adult brains is always very low (33). HtrA1 also colocalizes with ␤-amyloid deposits in human brain samples.…”
Section: Colocalization Of Htra1 and Amyloid Deposits In Human Brain mentioning
confidence: 92%
“…The functions of other HtrA members are not yet well-understood; however, it has been proposed that they may degrade misfolded, aggregated, or damaged proteins in suboptimal conditions such as during stress (Clausen et al, 2002). HtrA1 expression was identified recently during mouse development (De Luca et al, 2004) and in several human tissues (De Luca et al, 2003), and high expression of HtrA1 was reported in the human placenta (Nie et al, 2003a). Of interest, significant up-regulation of HtrA3 expression was also identified during placentation in the mouse (Nie et al, 2003b), suggesting that HtrA proteases might play important roles in placental development and function.…”
Section: Introductionmentioning
confidence: 96%
“…12 HtrA1, HtrA3 and HtrA4 are secreted proteases. Ubiquitously expressed in normal human adult tissues, 13 HtrA1 contains in addition to a highly conserved protease domain (trypsin like serine protease domain), an insulin growth factor-binding domain, a kazal type S protease inhibitor domain followed by one or two post-synaptic disclarge zona domains and a follistatin-like domain. 10 There is increasing evidences that HtrA1 regulates several physiological and pathological processes including tumour development, 14 Alzheimer's disease (AD), 15 placentation, 16 age-related macular degeneration 17 and osteoarthritis.…”
mentioning
confidence: 99%